"And all of a sudden my life was gone…": A biographical analysis of highly engaged adult gamers. (August 2015) - Domahidi, Emese; Quandt, Thorsten
Highly engaged gaming and its potentially adverse effects have been the subject of ongoing debate in media and science, most commonly in relation to problematic playing behaviours among adolescents. Although adult gamers are also known to be vulnerable to addictive playing behaviours, this aspect of highly engaged gaming among adults has rarely been investigated. To address this issue, biographical interviews were conducted with 35 adult gamers to explore their interaction with the game, integration of gaming into everyday life, and social interaction in real and virtual life. Participants were also asked about their reasons for becoming involved in highly engaged gaming, and for ending that involvement. The findings indicate that highly engaged adult gamers are a heterogeneous group. Three general types of gamer emerged from the interviews. One of these types showed no signs of problematic behaviour; however, the other two types tended to neglect aspects of everyday life and the real-life social environment in their playing behaviours.